2008
DOI: 10.1039/b713326j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural instability of the chemically delithiated (1 – z) Li[Li1/3Mn2/3]O2·(z) Li[Co1–yNiy]O2(0 ≤ y ≤ 1 and 0 ≤ z ≤ 1) solid solution cathodes

Abstract: The delithiated samples obtained by chemically extracting lithium from a series of O3 type layered (1 2 z) Li[Li 1/3 Mn 2/3 ]O 2 ?(z) Li[Co 12y Ni y ]O 2 solid solution samples by reacting with the oxidizer NO 2 BF 4 in acetonitrile medium have been chemically and structurally characterized. The oxygen loss in the delithiated samples has been found to be determined by the amount of lithium in the transition metal layer of the O3 type layered structure. However, high Mn 4+ content in the samples causes a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…Recently, many researchers demonstrated that the internal mechanical stress, originated form abrupt lattice shrinkage in the c ‐direction induced by the phase transition from H2 to H3, should take responsibility for the microcracks generation and propagation, which allows the penetration of electrolyte as well as exposing the internal surface where electrolyte attack and side reactions occur, and further aggravating the bulk structural and mechanical degradation of Ni‐rich cathodes . More importantly, as revealed by previous studies, structural degradation of NCM during cycling always accompanies the decreasing of Ni 3+ concentration . However, the distributions of the Ni 3+ concentration at particle level, whether the degrees of such surficial chemical changes are consistent among different secondary particles or different parts of the same particle, have not been thoroughly studied so far.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, many researchers demonstrated that the internal mechanical stress, originated form abrupt lattice shrinkage in the c ‐direction induced by the phase transition from H2 to H3, should take responsibility for the microcracks generation and propagation, which allows the penetration of electrolyte as well as exposing the internal surface where electrolyte attack and side reactions occur, and further aggravating the bulk structural and mechanical degradation of Ni‐rich cathodes . More importantly, as revealed by previous studies, structural degradation of NCM during cycling always accompanies the decreasing of Ni 3+ concentration . However, the distributions of the Ni 3+ concentration at particle level, whether the degrees of such surficial chemical changes are consistent among different secondary particles or different parts of the same particle, have not been thoroughly studied so far.…”
Section: Introductionmentioning
confidence: 97%
“…However, the energy densities of commercial Li-ion batteries using LiCoO 2 as a cathode cannot satisfy the demand of many of these applications [6][7][8][9][10]; new high-capacity cathode materials are therefore required. The layered Li-rich materials in the Li-Mn-Ni oxide system, which have higher energy densities (~250 mAh g −1 ) than other cathode materials such as LiCoO 2 [11][12][13][14][15][16][17][18], have attracted significant attention as promising new cathode materials. However, major drawbacks such as poor rate capability owing to insufficient electronic and ionic conductivities [19][20][21] have prevented their use in commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion batteries are essential power sources for portable electronic devices, electric vehicles, and smart grid storage systems [1][2][3][4][5][6][7][8]. These and other industrial developments have created an increased demand for advanced lithium batteries, which feature a high-performance cathode as the key component [9][10][11][12][13][14][15]. Ni-rich compounds, e.g., Li[Ni 0.8 Co 0.15 Al 0.05 ]O 2 , are promising cathode materials with high specific discharge capacity.…”
Section: Introductionmentioning
confidence: 99%